Strategy for integrating data on demographic to accelerate digital transformation in Makassar City, Indonesia - Andi Fitri Rahmadany; Mansyur Achmad; Ika Sartika (Department of Government Studies, Universitas Muhammadiyah Makassar, 2025)
This study examines Makassar, Indonesia, as an example of accelerated demographic data integration. The uniqueness of this study lies in the application of SWOT-based diagnostics in qualitative research to map, within a single analytical framework, the conditions that facilitate and the obstacles that shape the speed and quality of data integration across various institutions. A qualitative approach was used to reveal and discuss strategies for accelerating demographic data integration to support digital transformation. The analysis shows that the application of information technology, inter-agency collaboration, and systematic human resource capacity building are determining factors for acceleration. The results of the study found that the main challenges include data privacy issues, system interoperability, and resistance to change. The contribution of this study provides insights into data integration strategies to support more effective and efficient digital transformation in the future.